Introducing carbon structural adjustment: Energy productivity and decarbonization of the global economy - Hargroves, Charlie; Desha, C.; von Weisaeker, E. (John Wiley & Sons, 2016)
In the 21st century, much of the world will experience untold wealth and prosperity that could not be conceived only some three centuries before. However as with most, if not all, of the human civilizations, increases in prosperity have accumulated significant environmental impacts that threaten to result in environmentally induced economic decline. A key part of the world's response to this challenge is to rapidly decarbonise economies, with options to achieve 60–80% improvements (i.e., in the order of Factor 5) in energy and water productivity now available and proven in every sector. Drawing upon the 2009 publication ‘Factor 5’, in this article we discuss how to realize such large-scale improvements, involving complexity beyond technical and process innovation. We begin by considering the concept of greenhouse gas stabilization trajectories that include reducing current greenhouse gas emissions to achieve a ‘peaking’ of global emissions, and subsequent ‘tailing’ of emissions to the desired endpoint in ‘decarbonising’ the economy. Temporal priorities given to peaking and tailing have significant implications for the mix of decarbonising solutions and the need for government and market assistance in causing them to be implemented, requiring careful consideration upfront. Within this context, we refer to a number of examples of Factor 5 style opportunities for energy productivity and decarbonization, and then discuss the need for critical economic contributions to take such success from examples to central mechanisms in decarbonizing the global economy.